2020
DOI: 10.1093/infdis/jiaa233
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal and Extra-Vaginal Bacterial Colonization and Risk for Incident Bacterial Vaginosis in a Population of Women Who Have Sex With Men

Abstract: Background Bacterial vaginosis (BV) is a common cause of vaginal discharge and associated with vaginal acquisition of BV-associated bacteria (BVAB). Methods We used quantitative polymerase chain reaction assays to determine whether presence or concentrations of BVAB in the mouth, anus, vagina, or labia before BV predict risk of incident BV in 72 women who have sex with men. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…2a). Interestingly, many of the species positively correlated with metabolites associated with term delivery, including Atopobium vaginae, G. vaginalis, Sneathia sanguinegens, C. aurimucosum, Mobiluncus curtisii, Actinomyces neuii, Ureaplasma urealyticum, Gemella haemolysans, several Prevotella species, Candidatus Lachnocurva vaginae (BVAB1 77 ), BVAB2 and BVAB3 were previously reported to be associated with negative outcomes, such as BV 31,[78][79][80][81] , preterm birth [14][15][16]18,82 and other adverse pregnancy [82][83][84] and neonatal 85 outcomes. We find a similarly paradoxical negative correlation between Staphylococcus epidermidis, previously shown to be associated with BV 86 and late-onset sepsis in preterm neonates 87 , and both tartrate and ethyl glucoside (ρ = -0.28, p = 0.00069; ρ = -0.26, p = 0.0015, respectively; Fig.…”
Section: A Network Of Microbe-metabolite Associations In Sptbmentioning
confidence: 98%
“…2a). Interestingly, many of the species positively correlated with metabolites associated with term delivery, including Atopobium vaginae, G. vaginalis, Sneathia sanguinegens, C. aurimucosum, Mobiluncus curtisii, Actinomyces neuii, Ureaplasma urealyticum, Gemella haemolysans, several Prevotella species, Candidatus Lachnocurva vaginae (BVAB1 77 ), BVAB2 and BVAB3 were previously reported to be associated with negative outcomes, such as BV 31,[78][79][80][81] , preterm birth [14][15][16]18,82 and other adverse pregnancy [82][83][84] and neonatal 85 outcomes. We find a similarly paradoxical negative correlation between Staphylococcus epidermidis, previously shown to be associated with BV 86 and late-onset sepsis in preterm neonates 87 , and both tartrate and ethyl glucoside (ρ = -0.28, p = 0.00069; ρ = -0.26, p = 0.0015, respectively; Fig.…”
Section: A Network Of Microbe-metabolite Associations In Sptbmentioning
confidence: 98%
“…Published reports to date suggest that the upper FRT shares some bacterial species with the lower FRT, which may act as a reservoir for both healthy commensal or pathogenic populations [11,50]. Additional possible routes of transmission and microbial seeding of the uterine cavity include hematogenous spread of gut and oral microbiota; oral and perianal mucosa of an individual and their sexual partners; and microbiota in semen [35,[52][53][54][55][56].…”
Section: The Upper Female Reproductive Tract (Frt) Microbiome and Gynecologic Cancersmentioning
confidence: 99%
“…The loss of estrogen in the vaginal epithelium either from natural menopause or the results of hormonal or cytotoxic cancer therapies induces a shift towards non-Lactobacillus dominant lower FRT microbiomes with increased abundance of anaerobes such as Gardnerella and Atopobium. In addition, there is evidence that other body sites including oral and perianal mucosa [52][53][54] and sexual partners [52,84] may act as a reservoir for the FRT microbiome, which needs to be taken into consideration when designing interventions. To date, interventions manipulating the FRT microbiome have not yet been explored in the setting of gynecologic cancers, and therapies targeting the lower FRT microbiome have been focused on treatment of vaginal microbial dysbiosis/bacterial vaginosis.…”
Section: Interventions Targeting the Frt Microbiome And Implications For Personalized Medicinementioning
confidence: 99%
“…identified two distinct Megasphaera sequence types in a study evaluating association of vaginal bacteria with the common dysbiotic condition, bacterial vaginosis (BV) [12] and validated these observations using targeted PCR assays in women with and without BV [13, 14]. Subsequently, several studies have reported the association of these two Megasphaera sequence types with BV using molecular approaches [15–26]. Megasphaera type 1 was shown to be useful for the molecular diagnosis of BV [13, 14, 18, 22, 27–31] and has been included as a target in commercially available nucleic acid amplification tests for the diagnosis of BV [28].…”
Section: Full-textmentioning
confidence: 99%
“…Our groups have previously isolated Megasphaera bacterial species [38][39][40] and have demonstrated that Megasphaera type 1 and type 2 bacterial isolates are susceptible to clindamycin and the nitroimidazoles used to treat BV including metronidazole, tinidazole and secnidazole [38,39]. Megasphaera species have also been detected in the human oral cavity [17,19,41,42], rectum [17,19], stool [43][44][45] and male genitourinary microbiome [46][47][48]. Here, we systematically characterize three novel Megasphaera species from the human genital tract including isolates previously designated as Megasphaera type 1 and type 2 and compare them to validly published Megasphaera species.…”
mentioning
confidence: 99%